HIV-Positive and HIV-Negative Women with Medicaid Have Similar Rates of Stillbirth and Preterm Birth - Kathryn D. Thompson; David J. Meyers; Yoojin Lee; Susan Cu-Uvin; Ira B. Wilson (Women's Health Reports, 2022)
Introduction: Women living with human immunodeficiency virus (WLHIV) may face additional challenges and differential birth outcomes when compared with women without human immunodeficiency virus (HIV). There is limited research to date studying birth outcomes among a nationally representative sample of WLHIV. This study compares stillbirth and prematurity rates between HIV-positive (HIV+) and HIV-negative (HIV?) mothers in the Medicaid program. Methods: We used 12 years (2001?2012) of Medicaid Analytic eXtract data. We included Medicaid claims from the 14 states with the highest prevalence of HIV: California, Florida, Georgia, Illinois, Louisiana, Massachusetts, Maryland, North Carolina, New Jersey, New York, Ohio, Pennsylvania, Texas, and Virginia. Primary outcomes were stillbirth and preterm birth. We used logistic regression models adjusting for age, race, Medicaid coverage, eligibility, substance use, rurality, comorbidities, and state fixed effects to compare differences in rates for women with and without HIV. Results: Our study included a total of 33,078 HIV+ and 7,663,758 HIV? pregnancies from Medicaid enrollees between 2001 and 2012. The proportions of stillbirths and preterm births were higher for HIV+ when compared with HIV? mothers (0.9% vs. 0.7% and 8.0% vs. 6.6%, p?<?0.0001). After adjusting for covariates, being HIV+ was not significantly associated with both stillbirth (odds ratio [OR]: 1.05) or prematurity (OR: 1.01). Black race was a strong independent predictor of both stillbirth and prematurity (OR: 1.99 and 1.51, p?<?0.01). Rurality and substance abuse were not associated with either outcome. Conclusions: After adjustment for relevant covariates, maternal HIV infection was not associated with increased rates of stillbirth or preterm birth in the Medicaid program in the United States. It is imperative that we understand and eliminate the clinical, social, and contextual factors that are responsible for the strong association between black race and poor perinatal outcomes that we observe.